Tuina for Enuresis in Children: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chiin Tong; Chiin Tong; Qida He; Qida He; Manin Ho; Zhenghong Zhong; Zhenghong Zhong; Qibiao Wu; Qibiao Wu; Qibiao Wu; Qibiao Wu; Min Chen; et al. (Frontiers Media S.A., 2022)
ObjectiveTo evaluate the effects of Tuina (massage) vs. non-Tuina traditional Chinese medicine (TCM) treatments on nocturnal enuresis in children.MethodsA systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted following the Preferred Reported Items for Systematic Review and Meta-analysis (PRISMA) guidelines. RevMan 5.3 software was used for meta-analysis.ResultsTwelve RCTs recruiting a total of 1,007 children were included. Meta-analysis results showed that, compared with non-Tuina TCM treatments, Tuina could significantly improve the total effective rate of children's enuresis [RR = 1.29, 95%CI (1.22-1.36), P < 0.00001]. The results of subgroup analyses indicated that the total effective rate of Tuina combined with acupuncture in the treatment of nocturnal enuresis was higher than acupuncture alone [RR = 1.24, 95%CI (1.12-1.37), P < 0.0001]. The total effective rate of Tuina in the treatment of enuresis in children was better than that of herbal medicine alone [RR = 1.45, 95%CI (1.31-1.61), P < 0.00001]. The total effective rate of Tuina combined with herbal medicine in the treatment of enuresis in children was better than that of herbal medicine alone [RR = 1.16, 95%CI (1.06-1.26), P = 0.0007]. No adverse reactions of Tuina were reported in all included studies.ConclusionFrom the available evidence, Tuina, or Tuina combined with non-Tuina TCM treatments (acupuncture, or herbal medicine) can improve the clinical outcome of children with enuresis, indicating Tuina is a promising treatment choice for children's enuresis. However, because of the intrinsic limitations of the included studies, more high-quality randomized controlled trials with longer follow-up are still needed to further confirm the efficacy and safety of Tuina in the treatment of nocturnal enuresis in children.